PELAKSANAAN PENGAWASAN IZIN TINGGAL TENAGA KERJA ASING DI KANTOR IMIGRASI KELAS I PEKANBARU - Engli Irma Siagian; Sujianto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
The existence of foreign workers is one that brings capital as investor and skilled employee, however the coming of foreign workers is one of the main problems in employment sector. From the dwelling misappropriation,overstay. To control the delling problem, immigration officer has an important role in controlling, as is this controlling will give security for employment and people in pekanbaru.This research is meant to know how the surveillance implementation which assigned by immigration officer in pekanbaru. This research uses concept of the theory of monitoring which explained by manullang. There are there steps of surveillance process which done : set the standard, make a survey, and make a corrective action in the surveillance implementation of employment dwelling in class I immigration Pekanbaru.This research uses qualitative approach with snowball sampling with interview,observation, and documentation as the data accumulation technic. Based on the reseach result, the surveillance implementation of employment dwelling in class 1 immigration pekanbaru has not been maximum. The obstacle factor is lack of human resource from immigration officer, lack of infrastructure, the distance of surveillance which has been done is too far, and lack of participation between institutions and communities.Key words : foreign workers dwelling permition, Monitoring